Australian mental health staff response to antipsychotic medication side effects – the perceptions of consumers. (2nd January 2016) - Morrison, P.; Meehan, T.; Stomski, N.J.
Abstract : Despite the impact of side effects on adherence to medication regimes, few previous studies have examined the personal concerns of those prescribed antipsychotic medications. This study explores consumer perceptions of the support they receive from mental health staff for antipsychotic medication side effects. Semi-structured interviews were used to elicit the perceptions of 10 mental health consumers in a community care setting in Australia. Content analysis was used to examine the transcripts, and the audio-recordings were replayed to identify important contextual cues. The analysis identified several main themes, including: the relationship between participants and clinicians; information about side effects; and the value of the case-management system. Most participants reported that health professionals appeared disinterested in the antipsychotic medication side effects they experienced and did not understand the detrimental impact of side effects on their lives. The participants were also not equipped with sufficient information about the care they received, the prescribed medications, and possible side effects. Most participants felt excluded from decisions about the care they received, which caused significant distress. Structures and strategies therefore should be developed to ensure that the views of mental consumers are taken into consideration in a more fulsome manner in delivering mental health care in the community.